Potential of Red Seaweed Juice in Reducing Blood Pressure and Lead Levels in Urine in Workers at Public Fuel Filling Stations - Kusumawati, Evi; Imanuddin, Imanuddin; Rofiqoh, Rofiqoh; Nadimin, Nadimin (Biology, Medicine, & Natural Product Chemistry, 2025)
Lead (Pb) pollution, primarily from fuel combustion, poses severe health risks, including hypertension and systemic poisoning. Gas station attendants are particularly vulnerable to Pb exposure due to occupational hazards. This study investigates the efficacy of red seaweed (Eucheuma spinosum) juice, rich in antioxidants and bioactive components, in reducing Pb levels in urine and lowering blood pressure among gas station workers in Kendari City, Indonesia. A quasi-experimental pre-post-test control group design was employed. Thirty gas station attendants were divided into three groups: control (P0), treatment with seaweed juice once daily (P1), and treatment with seaweed juice twice daily (P2), each receiving 200 mL for two weeks. Urinary Pb levels and blood pressure were measured pre-and post-intervention. Phytochemical analysis of the seaweed juice confirmed the presence of antioxidants, phenolics, saponins, flavonoids, and triterpenoids. Data were analyzed using One-Way ANOVA and Kruskal-Wallis tests. The P1 and P2 groups exhibited a reduction in urinary Pb levels, whereas the P0 group showed an increase. However, statistical analysis indicated no significant differences in mean urinary Pb levels among groups. Blood pressure decreased in all groups, with the P2 group showing the most significant reduction in systolic pressure. Despite these trends, no statistically significant differences in blood pressure across the groups were observed. Red seaweed juice demonstrated potential in reducing Pb levels and improving blood pressure among gas station attendants. While statistical significance was not achieved, the findings suggest further research with larger sample sizes and longer intervention durations to confirm the therapeutic benefits of seaweed-based functional foods in mitigating Pb-related health risks.